Microbial cementation of ureolytic bacteria from the genus Bacillus: A review of the bacterial application on cement-based materials for cleaner production - Wong L.S. (Elsevier Ltd, 2023)
Abstracting; Bacilli; Bacteria; Bacteriology; Biodegradability; Biomineralization; Calcite; Carbon dioxide; Cementing (shafts); Cements; Construction industry; Cracks; Global warming; Heavy metals; Metabolism; Pollution control; Surface treatment; Sustainable development; Urea; Calcite precipitation; Calcium concentration; Cement based material; Environmental issues; Environmental threats; Global warming and climate changes; Microbial cementation; Polluting substances; Cement industry; Bacillus (bacterium); Bacteria (microorganisms); Lactobacillus casei